2019
DOI: 10.3390/atmos10110709
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Optical Depth of the Main Aerosol Species over Italian Cities Based on the NASA/MERRA-2 Model Reanalysis

Abstract: The Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2) provides data at 0.5° × 0.625° resolution covering a period from 1 January 1980 to the present. Natural and anthropogenic aerosols are simulated in MERRA-2, considering the Goddard chemistry, aerosol, radiation, and transport model. This model simulates the sources, sinks, and chemistry of mixed aerosol tracers: dust, sea salt, hydrophobic and hydrophilic black carbon and organic carbon, and sulfate. MERRA-2 aerosol reanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This climatology is now obsolete. Since the beginning of the century, AOD in Europe generally decreased by amount depending on the location but sometimes as much as 0.05 for average AOD typically about 0.2 (Filonchyk et al 2019;Rizza et al 2019). The Kinne climatology may thus overestimate AOD for recent years.…”
Section: Aerosol Optical Propertiesmentioning
confidence: 99%
“…This climatology is now obsolete. Since the beginning of the century, AOD in Europe generally decreased by amount depending on the location but sometimes as much as 0.05 for average AOD typically about 0.2 (Filonchyk et al 2019;Rizza et al 2019). The Kinne climatology may thus overestimate AOD for recent years.…”
Section: Aerosol Optical Propertiesmentioning
confidence: 99%
“…It has been estimated that 10% of the Saharan dust amount is transported across the Mediterranean Sea to Europe [6,7] in episodic storms or following periodic patterns [8,9]. In recent studies [10,11], it was reported an average contribution between 30% and 40% to the optical depth over different cities in southern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, atmospheric parameters may affect UVB and UVA irradiance in a different way at different locations (e.g., Fountoulakis et al, 2020). Recent studies have shown that atmospheric parameters which affect significantly solar UV radiation, such as clouds (Manara et al, 2016;Manara et al, 2015;Mateos et al, 2011;Pfeifroth et al, 2018) and aerosol (Orza and Perrone, 2015;Rizza et al, 2019;Di Ianni et al, 2018;Putaud et al, 2014;Masiol et al, 2017;di Sarra et al, 2008) have changed in Italy in the last decades, either on a regional or on a country scale. Although in Italy long-term continuous solar spectral UV (Diémoz et al, 2011) and total ozone measurements (Siani et al, 2018) are available from different stations across the country, they have never been used to study the long-term changes of UV irradiance at the surface, and how they are affected by changes in total ozone.…”
Section: Introductionmentioning
confidence: 99%